The essential functions of NEDD8 are mediated via distinct surface regions, and not by polyneddylation in Schizosaccharomyces pombe. - David Girdwood; Dimitris P Xirodimas; Colin Gordon (PLoS ONE)
The ubiquitin-like protein NEDD8 is highly conserved in eukaryotes, from man to Schizosaccharomyces pombe. NEDD8 conjugation to cullin proteins is a prerequisite for cullin based E3 ubiquitin ligase activity, and essential for S. pombe viability. Here, we have performed alanine scanning mutagenesis of all conserved surface residues and show that the majority of essential residues were located around the hydrophobic patch and the C-terminus. However, we further identified essential residues not previously reported to be involved in ubiquitin ligase regulation that importantly do not prevent Ned8p conjugation. We also find that mutation of all conserved lysine residues in Ned8p, did not affect yeast viability, suggesting that mono-neddylation is sufficient for yeast viability under most conditions.